GOLD RECOVERY OF REFRACTORY SULFIDE CONCENTRATES USING DIRECT CYANIDE LEACHING WITH NITRITE AS AN OXIDANT - Suratman Suratman (Indonesian Mining Journal, 2016)
The problem of refractory sulfide gold ore that has a gold recovery less than 50% when direct cyanidation applied, still exists until now. It needs oxidative pretreatment for cyanidation to be effective in gold recovery the objective of this study is figuring out the effect of sodium nitrite as an oxidizing reagent on cyanidation of refractory gold ore. Cyanide leaching of the concentrate was performed at 20%-w/w of solid (500 gram of refractory sulfide gold ore concentrate) in a 2.5-liter glass reactor with aeration and stirred at 250 rpm. Leach solutions were prepared using deionized-distilled water at the prescribed concentration of reagents. Recovery of gold increased gradually to its maximum value of 93.05% as the value of cyanide strength increased from 0.8 to 1.2% and the addition of sodium nitrite raise to 1.2 M. No improvement for further addition of nitrites. This introduction of new hydrometallurgical pre-treatment process has given more option for treating refractory ores.